Presentation: Symbols, Rituals and Identities - Grández Moreno, Félix (1997)
Allpanchis reaches its 50th issue and offers its readers a group of collaborations gathered under the title Symbols, rituals and identities. The title evokes a very important issue for the magazine and for the Instituto de Pastoral Andina. The publication of studies and research advances on the symbolic world in the Andes has been a constant in the almost three decades of Allpanchis. On this occasion we have brought together six works that return to the subject from different approaches and disciplines: anthropology, history, theology, linguistics and literary criticism.